Assessing the Factors In uencing Water Use in Austin, TX - Friend, Jesse; Wilson, Cyril O.; Running, Garry L. (My University, 2018)
Water plays an important role in domestic, agricultural and industrial domains and therefore its supply and quality are crucial to maintain. Water supply can be influenced by a number of factors with potential implications for its quality and availability. The goal of this project is to examine the spatial patterns of water use in Austin, TX and gauge the factors influencing its use. Key demographic variables are regressed on water use data in a bid to give insight on the factors affecting the spatial and temporal patterns of water use in the study area. Demographic variables utilized include median household income, size of household, average parcel size, and microclimate data. This project is important, as climate change will continue to modify our world, making sustainable resource use much more crucial to a nation. Understanding the factors of water use will provide functional knowledge to adjust policies and practices of people around the country. This project will help to determine what accounts for water use in Austin, TX. The results show that water use in Austin is influenced by (>70%) factors not included in this study. However, average parcel size, household size, and median household income are all shown to be statistically significant explanatory variables. Individuals and policy makers can use this information to adapt their future water use to more sustainable practices.
Color poster with text, charts, maps, and graphs
Keywords: Water consumption--Texas; Posters